Population-based seroprevalence of SARS-CoV-2 and the herd immunity threshold in Maranhão - Silva, Antônio Augusto Moura da; Lima-Neto, Lídio Gonçalves; Azevedo, Conceição de Maria Pedrozo e Silva de; Costa, Léa Márcia Melo da; Bragança, Maylla Luanna Barbosa Martins; Barros Filho, Allan Kardec Duailibe; Wittlin, Bernardo Bastos; Souza, Bruno Feres de; Oliveira, Bruno Luciano Carneiro Alves de; Carvalho, Carolina Abreu de; Thomaz, Erika Barbara Abreu Fonseca; Simões-Neto, Eudes Alves; et al. (Revista de Saúde Pública, 2020)
OBJECTIVE: To estimate the seroprevalence of SARS-CoV-2 in the state of Maranhão, Brazil. METHODS: A population-based household survey was performed, from July 27, 2020 to August 8, 2020. The estimates considered clustering, stratification and non-response. Qualitative detection of IgM and IgG antibodies was performed in a fully-automated Elecsys® Anti-SARS-CoV-2 electrochemiluminescence immunoassay on the Cobas® e601 analyzer (Roche Diagnostics). RESULTS: In total, 3,156 individuals were interviewed. Seroprevalence of total antibodies against SARS-CoV-2 was 40.4% (95%CI 35.6-45.3). Population adherence to non-pharmaceutical interventions was higher at the beginning of the pandemic than in the last month. SARS-CoV-2 infection rates were significantly lower among mask wearers and among those who maintained social and physical distancing in the last month compared to their counterparts. Among the infected, 26.0% were asymptomatic. The infection fatality rate (IFR) was 0.14%, higher for men and older adults. The IFR based on excess deaths was 0.28%. The ratio of estimated infections to reported cases was 22.2. CONCLUSIONS: To the best of our knowledge, the seroprevalence of SARS-CoV-2 estimated in this population-based survey is one of the highest reported. The local herd immunity threshold may have been reached or might be reached soon.